THE INFLUENCE OF HALAL PRODUCT IMAGE, PRODUCT DESIGN, AND MARKETING STRATEGY ON CONSUMER LEVELS IN HALAL COSMETIC PRODUCTS (CASE STUDY ON SAFI) - Nispawatil Isnaini; Alifia Nur Zaida; Khusnul Zulmiati (Universitas Airlangga, 2021)
The halal industry is an innovation in the business world that can increase economic growth in Indonesia. The halal industry market in Indonesia is now growing rapidly and has become an alternative choice among the public. Several industrial sectors that support the development of the halal industrial market include banking, food and beverage, Muslim fashion, health, and cosmetics. The topic that is the focus of this research is the cosmetics industry which has been certified halal. Halal cosmetics are one of the halal products that are being discussed and sought after by many people. In Indonesia, the halal cosmetics industry continues to experience significant development. Public interest in halal cosmetics is increasing along with public awareness of the importance of using halal products, especially cosmetic products. In order to meet the increasing consumer demand for halal cosmetic products, of course, producers will make various efforts to be able to provide quality products. Efforts to improve the quality of this product are aimed at maintaining and increasing consumer confidence in the halal cosmetic products he has chosen. Talking about efforts to increase consumer confidence in halal cosmetic products, there are several supporting factors that need to be studied. Therefore, in this study the researcher wanted to analyze the effect of the image of halal products, product design, and marketing strategies on the level of consumer confidence in halal cosmetics. This research is more focused on one of the brands of halal cosmetic products, namely Safi, where its products are well known by the wider community. The theoretical framework in this study uses the TOE (Technology, Organization, Environment) framework approach where each independent variable that affects is correlated with this concept. The method used is a quantitative method. Data collection was carried out by distributing questionnaires to respondents, in this case the consumers of Safi halal cosmetic products in Indonesia. This research was conducted using non-probability techniques. The test of this research is that the authors use SPSS 25.